2022
DOI: 10.3390/cells11060983
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of microRNAs in Regulating Cardiomyocyte Death

Abstract: microRNAs (miRNA, miRs) play crucial roles in cardiovascular disease regulating numerous processes, including inflammation, cell proliferation, angiogenesis, and cell death. Herein, we present an updated and comprehensive overview of the functional involvement of miRs in the regulation of cardiomyocyte death, a central event in acute myocardial infarction, ischemia/reperfusion, and heart failure. Specifically, in this systematic review we are focusing on necrosis, apoptosis, and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 151 publications
1
19
0
Order By: Relevance
“…We and others have shown that microRNAs (miRNAs), small non-coding RNAs of ~22 nucleotides, may serve as reliable biomarkers of various human disorders (Keller et al, 2014;Santulli et al, 2014;Sardu et al, 2014;Novak et al, 2015;Santulli, 2015;Santulli, 2016;Cammarata et al, 2018;Slota and Booth, 2019;Dama et al, 2020;Donati et al, 2021;Jankauskas et al, 2021;Kanach et al, 2021;Kansakar et al, 2022). Therefore, the microRNAs profile could be a promising biomarker candidate…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We and others have shown that microRNAs (miRNAs), small non-coding RNAs of ~22 nucleotides, may serve as reliable biomarkers of various human disorders (Keller et al, 2014;Santulli et al, 2014;Sardu et al, 2014;Novak et al, 2015;Santulli, 2015;Santulli, 2016;Cammarata et al, 2018;Slota and Booth, 2019;Dama et al, 2020;Donati et al, 2021;Jankauskas et al, 2021;Kanach et al, 2021;Kansakar et al, 2022). Therefore, the microRNAs profile could be a promising biomarker candidate…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The proangiogenic properties of miR-548j-5p have been demonstrated to exert a beneficial effect on hindlimb ischemia in mouse models [ 50 ]. Many miRNAs have also been identified to be involved in various types of cardiomyocyte death, making them interesting therapeutic targets in ischemic events such as acute myocardial infarction and heart failure [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRs) are small non-coding RNAs molecules of 18-24 nucleotides, which typically repress messenger RNAs (mRNAs) by binding their 3′ untranslated region (Santulli, 2015;Fridrichova and Zmetakova, 2019;Stavast and Erkeland, 2019;Hu et al, 2021;Mirzaei et al, 2021;Mone et al, 2021b;Bielska et al, 2022;Karagiannopoulos et al, 2022;Mauro et al, 2022;Moisoiu et al, 2022;Qiu et al, 2022;Traber and Yu, 2022;Yaylim et al, 2022;Zeng et al, 2022). Substantial evidence has shown that miRs exert their activity in many biological processes and several miRs have been proposed as biomarkers and potential targets of novel therapeutic strategies (Creemers et al, 2012;Wronska et al, 2015;Barwari et al, 2016;Zarone et al, 2017;Chen et al, 2018;Wong et al, 2018;Morelli et al, 2019;Kawasaki et al, 2020;Wang et al, 2020;Fonseca et al, 2021;Gambardella et al, 2021;Bonnet et al, 2022;Gambardella et al, 2022a;Gambardella et al, 2022b;Kansakar et al, 2022;Varzideh et al, 2022). Several investigators have linked miRs to frailty for their involvement in inflammation, endothelial dysfunction, and senescence (Quinn and O'Neill, 2011;Olivieri et al, 2012;Geiger and Dalgaard, 2017;Rusanova et al, 2019;Bu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%